The Role of Sembung (Blumea balsamifera) Leaf Extract in Preventing Atherosclerosis in Hyperlipidemia Rat Models - I Made Jawi; I Wayan Putu Sutirta Yasa; I Gede Widhiantara; Anak Agung Ngurah Subawa; Putu Angga Wiradana; Naw, Sin War (Biosaintifika: Journal of Biology & Biology Education, 2024)
This study aims to prove that administering BBLE as a natural antioxidant can prevent atherosclerosis by maintaining lipid profiles, antioxidant enzymes, and netrin-1 levels in hyperlipidemia in rat models. The research subjects were 20 adult male Wistar rats (Rattus norvegicus), which were divided into 2 groups using a randomized pretest and posttest control group design. Before treatment and after treatment for 3 months, lipid profiles, MDA, SOD, and netrin-1  were examined. The control group was only given high-cholesterol diets (HCD), while the treatment, apart from HCD, was also given BBLE 4mg/day. The data obtained was tested using paired t-test and group t-test. The results of the study showed that there was a significant decrease in netrin-1 in the control group (p<0.05) after being given HCD for three months. In the treatment group, it also decreased but it was not significant (p>0.05). Netrin-1 levels in the treatment group were higher than the control (p<0.05). The lipid profile experienced a significant increase in HDL in the treatment group accompanied by a significant decrease in MDA and an increase in SOD (p<0.05) when compared with the control group. This study concludes that administering BBLE at a dose of 4 mg/day to rats given HCD caused an increase in netrin-1 levels accompanied by improvements in lipid profiles and prevention of oxidative stress. The findings of this study reveal the novelty of BBLE in treating and maintaining blood vessel function in mice given HCD by increasing netrin-1 levels.